KEWAJIBAN NEGARA DALAM MENCEGAH PELANGGARAN HAM OLEH KORPORASI MULTINASIONAL - Natamiharja, Rudi; Setiawan, Ikhsan; Khoirunisya, Siti (Faculty of Law, Universitas Tanjungpura, 2025)
Abstract The increasing activities of multinational corporations have significantly impacted human rights (HR), both positively and negatively. On the one hand, corporations contribute to the global economy; on the other hand, their activities are often associated with human rights violations, particularly in developing countries. This study aims to analyze the state